2019
DOI: 10.1038/s41598-018-37843-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of relationship between vitamin D status and reproductive fitness in Scottish hill sheep

Abstract: There is a growing interest in the influence of vitamin D on ovine non-skeletal health. The aim of this study was to explore the relationship between pre-mating vitamin D status, as assessed by serum concentrations of 25-Hydroxyvitamin D [25(OH)D; comprising D2 and D3] and subsequent reproductive performance of genetically unimproved Scottish Blackface (UBF), genetically improved Scottish Blackface (IBF) and Lleyn ewes kept under Scottish hill conditions. 25-Hydroxyvitamin D2 (25(OH)D2) and 25-Hydroxyvitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 57 publications
(71 reference statements)
4
16
1
Order By: Relevance
“…Our study discovered that host factors are associated with vitamin D status in cattle. Similar to our observations in sheep in temperate regions 27,28 , we found that dark coat colour was associated with lower serum 25(OH)D 3 concentrations in African calves which we would predict is a result of lower cutaneous production of vitamin D. Our study failed to identify clear genetic loci associated with serum 25(OH)D concentrations in cattle. This observation mirrors findings in humans which have also shown that total 25(OH)D concentration is under polygenic control with only a modest number of genetic loci linked to vitamin D status 38,39 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study discovered that host factors are associated with vitamin D status in cattle. Similar to our observations in sheep in temperate regions 27,28 , we found that dark coat colour was associated with lower serum 25(OH)D 3 concentrations in African calves which we would predict is a result of lower cutaneous production of vitamin D. Our study failed to identify clear genetic loci associated with serum 25(OH)D concentrations in cattle. This observation mirrors findings in humans which have also shown that total 25(OH)D concentration is under polygenic control with only a modest number of genetic loci linked to vitamin D status 38,39 .…”
Section: Discussionsupporting
confidence: 82%
“…The relationship between vitamin D and non-skeletal health outcomes has been less studied in ruminants. We have previously reported a positive association between autumnal serum 25(OH)D concentrations and subsequent fecundity 27 and birth weight 28 the following spring in sheep. Vitamin D metabolites have been shown to modulate bovine immune cell phenotype in-vitro [29][30][31][32] and in-vivo 33,34 .…”
mentioning
confidence: 92%
“…Subsequently, a study by Zhou et al (2019) examined reproductive traits and vitamin D status in Scottish hill sheep. This study observed no significant association between ewe vitamin D status and number of lambs born or weaned, however concentrations of 25(OH)D3 and total 25(OH)D were positively associated with birth weight of single and twin lambs [91]. Conversely, a recent study on a flock of Romney sheep in New Zealand revealed a negative correlation between total 25(OH)D concentration and ewes that were pregnant with triplets, with no association detected between vitamin D status and ewes pregnant with single or twin lambs [90].…”
Section: Sheep and Goatscontrasting
confidence: 75%
“…This is likely the result of breed skin pigmentation differences, with the Romney sheep of New Zealand having minimal skin pigmentation in comparison to the Soay sheep and the Scottish Blackface sheep which both have dark skin and significant pigmentation. Comparing the Scottish breeds in the study by Zhou et al, the concentration of 25(OH)D3 and total 25(OH)D was significantly higher in Lleyn ewes, which have light pigmentation and white faces and legs, in comparison with Scottish Blackface ewes which have dark pigmentation and black faces and legs [91]. Combined, these results support the findings from Handel et al (2016) that sheep coat colour impacts vitamin D3 status [30].…”
Section: Sheep and Goatssupporting
confidence: 75%
See 1 more Smart Citation